BAKTERI M2 PENGHASIL PHB (Polyhydroxybutirate) YANG DIISOLASI DARI PULAU LAKI, KEPULAUAN SERIBU - Supryati, Dyah (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Polyhydroxybutirate Producing Bacteria M2 Isolated From Pulau Laki, KepulauanSeribu. PHB is one of very important material for production of biodegradable plastic,and physiologically it is important electron sink in anaerobic-aerobic process. PHBÃ‚Â accumulating bacteria M2 was isolated from mangrove of Pulau Laki, Kepulauan Seribu.The bacteria were able to produce PHB from glucose, acetate, and sucroseÃ‚Â .Strain M2 was produced PHB (79.9% of biomass) by using acetate as sole carbonÃ‚Â sources. The strain was also able to grow at 3 % to 5 % with a doubling time of 10.9 andÃ‚Â 21.04 hours and specific growth rate (0.0633 h-1 and 0.0328 h-1). The ability of Strain M2Ã‚Â to produce PHB and its salinity tolerance implying that this strain is not only importanceÃ‚Â for PHB production but also ecologically importance microbe.Key word: PHB accumulating bacteria, marine, salinity tolerance